Датчик угла поворота генераторного типа с элементом на поверхностных акустических волнах - Lepikh, Ya. I. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
The results of developing an intelligent rotation angle sensor with a surface acoustic wave (SAW) element are presented. A structural diagram of a generator-type sensor is described, in which the SAW element serves as the corresponding delay line. The main characteristics of the sensor are presented, and its application area is shown.